A Partially Protective Vaccine for Fasciola hepatica Induced Degeneration of Adult Flukes Associated to a Severe Granulomatous Reaction in Sheep - Molina-Hernández, Verónica; Ruiz-Campillo, María Teresa; Martínez-Moreno, Francisco Javier; Buffoni, Leandro; Martinez Moreno, Álvaro; Zafra, Rafael; Bautista, María José; Escamilla-Sánchez, Alejandro; Pérez-Caballero, Raúl; Pérez, José (MDPI, 2021)
Fasciolosis is a parasitic disease of livestock causing important economic losses worldwide and it is also a zoonosis. Current therapy relies on the use of anthelmintic drugs, which is no longer sustainable due to the increase of anthelmintic resistance and the risk of drug residues in food. A deep understanding of the host-parasite interaction is required to develop protective vaccines for the control of fasciolosis. The aim of the present study is to evaluate the hepatic lesions in sheep vaccinated with a partly protective vaccine for F. hepatica, a non-protective vaccine and an infected control group. The protective vaccine showed less severe hepatic lesions than the infected control group. In addition, in the protective vaccine group dead flukes surrounded by a severe granulomatous inflammation were observed, which taken together with the lower fluke burden, suggests that the host response induced by the partially protective vaccine may have been involved in the death of adult flukes of F. hepatica. This is the first study reporting the presence of degenerated flukes associated to a severe granulomatous inflammation in bile ducts in a vaccine trial, a finding that would be useful for improving vaccine efficacy in future trials.
Keywords: Histología; Histology; Immunopathology; Parasitology